Health Care Utilization and Costs Associated With Acute Pancreatitis. Issue 3 (March 2017) - Wadhwa, Vaibhav; Patwardhan, Soumil; Garg, Sushil K.; Jobanputra, Yash; Lopez, Rocio; Sanaka, Madhusudhan R.
Abstract : Objective: Acute pancreatitis is a common inpatient diagnosis among gastrointestinal disorders. The aim of this study was to evaluate the incidence of inpatient admissions, costs, and mortality rates associated with acute pancreatitis in the United States. Methods: We analyzed the National Inpatient Sample for all patients in which acute pancreatitis ( International Classification of Diseases, Ninth Revision code: 577.0) was the principal discharge diagnosis during the period 1997–2012. The statistical significance of the difference in the hospital discharges, length of stay, and costs over the study period was determined by utilization of regression analysis. Results: In 1997, there were 164, 776 admissions with a principal discharge diagnosis of acute pancreatitis as compared with 275, 170 in 2012 ( P < 0.001). The mean length of stay for acute pancreatitis decreased from 6.4 days in 1997 to 4.7 days in 2012 ( P < 0.001). However, during this period, the mean hospital charges increased by 118.6% from 15, 433 in 1997 to 33, 744 in 2012 ( P < 0.001). The in-hospital mortality rate decreased significantly from 1.9% in 1997 to 0.78% in 2012 ( P < 0.001). Conclusions: Inpatient admissions for acute pancreatitis and associated costs have increased markedly over the last 16 years in the United States. However, the lengths of stay and mortality rates have decreased significantly.